The Quest of Identity of Kafka Tamura in Haruki Murakami’s Kafka on The Shore - Nita Nurul Ramadhita (Universitas Pendidikan Indonesia (UPI), 2015)
In order to explore the issue of identity construction of an adolescent character in Haruki Murakami’s Kafka on the Shore, this research uses Nikolajeva’s (2003) theory on implicit characterization and Trites’s (2000) theory on identity construction in young adult literature. By employing a narrative approach in a qualitative method which focuses on the analysis of the main character, Kafka Tamura, and his quest of identity, the findings reveal three main points. First, through the implicit characterization depicted in his preferences, Kafka is portrayed as a teenager who distances himself from the society. Second, the most prominent issue in Kafka’s quest of identity is triggered by father-centered conflicts. Third, sex and death in this novel are used as conflicts resolution. From the analysis, it can be concluded that the identity constructed by Kafka in the end of the novel is a compromised identity who learns to accept the norms and values of the society he intends to leave. Keywords: Adolescent, coming-of-age, identity construction, young adult literature